2014
DOI: 10.1007/s10735-014-9569-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of TBX2 expression in non-small cell lung cancer

Abstract: T-box2 (TBX2) expression has been reported to be related to aggressive tumor features. However, the role of TBX2 in non-small-cell lung cancer (NSCLC) tumorigenesis has never been elucidated. So we aimed at investigating the potential role of TBX2 in NSCLC. TBX2 expression was evaluated by qRT-PCR and Western blotting in 50 paired fresh lung cancer tissues as well as immunohistochemistry on 212 paraffin-embedded sections. We showed that the expression level of TBX2 was significantly increased in NSCLC as compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…Up-regulation of TBX2 has been reported in a wide range types of cancer [ 13 19 ]. In the present study, we reported that TBX2 mRNA and protein expression was significantly higher in NPC tissues samples than that in the adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up-regulation of TBX2 has been reported in a wide range types of cancer [ 13 19 ]. In the present study, we reported that TBX2 mRNA and protein expression was significantly higher in NPC tissues samples than that in the adjacent normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidences have linked TBX2 to tumorigenesis. TBX2 expression is up-regulated in a wide range of cancers, including melanoma [ 13 ], pancreatic cancer [ 14 ], bladder cancer, breast cancer [ 15 – 17 ], colorectal cancer [ 18 ] and lung cancer [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that most of those probes identified in 7 cancers are located in non-island regions. Moreover, some genes of those CpG sites located have been reported to be associated with the prognosis of various cancers (such as SHANK2 [31], LTBP1 [32], GRIA4 [33], OSR2 [33], PHLDB2 [34], TBX2 [35][36][37] and GPR37 [38]). Currently, no qualified independent dataset is available for systematically estimating the reproducibility and validity of the probe-based prognostic classifier, thus a further verification of this prognostic model would be necessary in the future.…”
Section: Prognostic Model Successfully Divides Patients Into High-rismentioning
confidence: 99%
“…Earlier reports have suggested that expression levels of TBX2 are elevated in NSCLC [ 39 , 40 ]. The reports by Hu et al [ 39 ] and Zhang et al [ 40 ] interrogated TBX2 protein by immunohistochemistry in NSCLCs alone (tissue microarrays) and suggested that tumors with relatively high expression of the protein (based on percent positivity within the tumors themselves) exhibited comparatively poor prognosis [ 39 , 40 ]. The same reports studied expression levels of the TBX2 gene (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The same reports studied expression levels of the TBX2 gene (e.g. by quantitative real-time PCR) in NSCLCs and paired normal lung tissues in a smaller subset of NSCLC cases ( n = 40 to 50) [ 39 , 40 ] demonstrating that the gene is elevated in the tumors. These earlier studies [ 39 41 ], albeit few, point to putative oncogenic roles and properties for the TBX2 gene in human NSCLC.…”
Section: Discussionmentioning
confidence: 99%